2019
DOI: 10.1038/s41467-019-12486-x
|View full text |Cite|
|
Sign up to set email alerts
|

A tool for functional brain imaging with lifespan compliance

Abstract: The human brain undergoes significant functional and structural changes in the first decades of life, as the foundations for human cognition are laid down. However, non-invasive imaging techniques to investigate brain function throughout neurodevelopment are limited due to growth in head-size with age and substantial head movement in young participants. Experimental designs to probe brain function are also limited by the unnatural environment typical brain imaging systems impose. However, developments in quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 132 publications
(122 citation statements)
references
References 32 publications
0
122
0
Order By: Relevance
“…Furthermore, the use of a MEG system with fixed helmet size renders the acquisition of high quality data and whole head coverage in young participants more challenging due to their reduced head size. Based on those latter considerations, further studies should rely on on-scalp neuromagnetometers such as optically pumped magnetometers, which have been demonstrated to be usable for lifespan neuromagnetic investigations 78 . Finally, we used a restricted, low-density connectome limited to major RSNs (to limit as much as possible the multiple comparison issue) to investigate the age-related changes in static functional integration.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 99%
“…Furthermore, the use of a MEG system with fixed helmet size renders the acquisition of high quality data and whole head coverage in young participants more challenging due to their reduced head size. Based on those latter considerations, further studies should rely on on-scalp neuromagnetometers such as optically pumped magnetometers, which have been demonstrated to be usable for lifespan neuromagnetic investigations 78 . Finally, we used a restricted, low-density connectome limited to major RSNs (to limit as much as possible the multiple comparison issue) to investigate the age-related changes in static functional integration.…”
Section: Results Of Static Rsfc Analyses Are In Line With Previous Stmentioning
confidence: 99%
“…One of the most exciting features of OPM sensors is that they can be arranged in arbitrary arrays. This means that they can be adapted to individual head shapes, making them more resilient against head movements, and they can be applied to children ( Hill et al., 2019 ). Recent studies have confirmed that the potential gain in the signal-to-noise ratio featured by the OPMs can improve the accuracy of source modelling ( Boto, Bowtell, Krüger, Fromhold, Morris, Meyer, Barnes, Brookes, 2016 , Zetter, Iivanainen, Stenroos, Parkkonen, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The development of quantum science and technology has allowed the development of wearable magnetoencephalography (MEG) technology that is likely to revolutionize electrophysiological measurements of brain activity. A lifespan-compliant system of MEG was demonstrated, which showed a new approach to functional imaging (Hill et al, 2019).…”
Section: Imaging Technologies Used For the Brainmentioning
confidence: 99%